2016
DOI: 10.1155/2016/1258504
|View full text |Cite
|
Sign up to set email alerts
|

ATP Induces IL-1βSecretion inNeisseria gonorrhoeae-Infected Human Macrophages by a Mechanism Not Related to the NLRP3/ASC/Caspase-1 Axis

Abstract: Neisseria gonorrhoeae (Ngo) has developed multiple immune evasion mechanisms involving the innate and adaptive immune responses. Recent findings have reported that Ngo reduces the IL-1β secretion of infected human monocyte-derived macrophages (MDM). Here, we investigate the role of adenosine triphosphate (ATP) in production and release of IL-1β in Ngo-infected MDM. We found that the exposure of Ngo-infected MDM to ATP increases IL-1β levels about ten times compared with unexposed Ngo-infected MDM (P < 0.01). H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 60 publications
1
10
0
Order By: Relevance
“…Previous study indicated that NG (P9-17 strain) induced IL-1β mRNA expression in human blood monocyte-derived macrophage; however, P9-17 strain did not induce IL-1β secretion. Notably, exogenous ATP treatment induced IL-1β secretion from P9-17 strain-infected cells (31). In addition, ATP-mediated IL-1β secretion did not through increasing the caspase-1 activation in P9-17 strain-infected cells, but may act through the vesicle trafficking or pore formation levels (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous study indicated that NG (P9-17 strain) induced IL-1β mRNA expression in human blood monocyte-derived macrophage; however, P9-17 strain did not induce IL-1β secretion. Notably, exogenous ATP treatment induced IL-1β secretion from P9-17 strain-infected cells (31). In addition, ATP-mediated IL-1β secretion did not through increasing the caspase-1 activation in P9-17 strain-infected cells, but may act through the vesicle trafficking or pore formation levels (31).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, exogenous ATP treatment induced IL-1β secretion from P9-17 strain-infected cells (31). In addition, ATP-mediated IL-1β secretion did not through increasing the caspase-1 activation in P9-17 strain-infected cells, but may act through the vesicle trafficking or pore formation levels (31). These results were conflicting with our and other findings, as NG strains: ATCC 49226 (this study), 1291 (32) and FA1090 (14) induced IL-1β secretion without additional ATP treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In this line, we think that the M2 phenotype promoted by gonococcus could be reverted using COX-2 inhibitor. We also showed no significant differences in IL-1β levels in MDM infected cells compared to non-infected MDM cells, suggesting that N. gonorrhoeae could trigger insufficient IL-1β levels to activate innate immune response (83). Then, we were able to promote the IL-1β processing and release using exogenous ATP.…”
Section: Opportunities and Challenges Of Therapeutics To Control Immumentioning
confidence: 75%
“…During infection, N. gonorrhoeae interact with immune cells such as macrophages. In macrophages N. gonorrhoeae is able to escape from phagosome (27, 42, 4548), modulate cellular iron metabolism (52, 53), inhibit apoptosis and autophagy (27, 60), modulate production of inflammatory/anti-inflammatory cytokines (6371, 83), and polarizes macrophages, resulting in macrophages that are less capable of T cell proliferation (45). CD86, Cluster of Differentiation 86; IL- 1, Interleukin 1; IL-10, Interleukin 10; MHC, Major Histocompatibility Complex; PD-L1, Programmed Death-Ligand 1; TGF-β, Transforming Growth Factor-beta; TNF-α, Tumor Necrosis Factor-alpha.…”
Section: Resultsmentioning
confidence: 99%
“…In innate immunity, P4 downregulates IFN-γ secretion in human peripheral blood natural killer cells ( Robinson and Klein, 2012 ) and weaken macrophage functions ( Franchi et al, 2012 ). In adaptive immunity, P4 suppresses the CD4 + T cells proliferation, inhibits the cytotoxic activity of CD3 + CD8 + T cells ( García et al, 2016 ), and interferes with the polarization of Th1/Th17 cells ( Andrabi et al, 2017 ). Therefore, the immune suppression ability of P4 suggests that it may participate in the pathogenesis of female asymptomatic gonococcal infections.…”
Section: Introductionmentioning
confidence: 99%